Effects of controlled atmosphere (CA) storage on pectinmethylesterase (PME) activity and texture of ‘Rocha’ pears - Galvis-Sánchez, Andrea C. (2001)
Firmness and pectinmethylesterase (PME) activity were evaluated in pears (cv Rocha) after 9 months of storage in controlled atmosphere (CA) followed by various periods of exposure to air at room temperature. The free calcium content was also evaluated in tissues. Fruit firmness decreased with increasing time of air exposure for all four different CA storage conditions tested. After 9 days of air exposure, fruits stored in 2% O2 + 1.5% CO2 were less firm than control fruits (stored in air) and showed higher PME activity. In spite of normal textural changes being observed with increasing time of exposure to air at room temperature, the underlying metabolism might have been affected by CA storage.